PLANNING FOR THE CONSTRUCTION OF PRAYER ROOMS AND PUBLIC TOILETS BY UTILIZING PLASTIC WASTE INTO ECO BLOCKS TO ADD FACILITIES AND SUPPORT THE SUSTAINABLE DEVELOPMENT MOVEMENT AT PREPAT BAY BEACH, PANGKALPINANG CITY - Abisa, Jotian; Nabila Karima; Muhammad Iqbal; Putri Nathasya Dhimastika (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2024)
This study analyzes the financial feasibility of the construction of prayer rooms and public toilets by utilizing used plastic waste converted into Eco Block in Taman Bunga, Pangkalpinang City. The analysis uses several financial valuation methods, including Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The results of the study showed that the project was financially feasible based on all the parameters evaluated. The development project, which is funded through the 2025 Pangkalpinang City Regional Expenditure Budget (APBD), is an innovative approach in sustainable infrastructure development by utilizing recycled plastic waste materials. This initiative not only meets the needs of public facilities but also contributes to environmental sustainability through waste management solutions